THE MEDIATING AND MODERATING EFFECT ON SMES' PERFORMANCE: DOES RELIGIOSITY MATTER? - Lestari, Wiwik; Lindiawati, Lindiawati; Ulum, Achmad Syaiful; Permana, Dhyka Bagus (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2023)
Small and medium enterprises (SMEs) are entities managed and controlled by the owners. The performance of the owners strongly reflects the business performance of the SMEs. That is also the way of looking into the study aiming at analyzing the performance of SMEs from an Islamic perspective, which can be viewed from the owners' religiosity and financial behaviour. This framework is still rarely found in shari'a economics literature. This also involves further consideration of the need for Islamic values on the performance of small businesses in countries with Muslim-majority. Using a survey research design, 238 small business owners and managers participated in responding to a self-registered questionnaire research instrument. Using PLS-SEM, the research instrument has been tested for its validity and reliability and the variable's influence. The result proves that religiosity does not directly affect the performance of SMEs but indirectly influences the performance through financial behaviour. It means that religiosity forms good financial behaviour, and then the financial behaviour increases business performance. This study also finds that gender moderates the effect of religiosity on the behaviour of SME owners or managers. Furthermore, business age reduces the effect of financial behaviour on performance. The results of this study warn that old businesses should not make SMEs owners feel comfortable and resistant to change unless they fail to gain good business performance.